From infectious diseases to chronic diseases: the paradigm shift of spatial epidemiology in disease prevention and control - Hu, Ke; Li, Chaojie; Yang, Xingjin; Ou, Shuiping; Zhang, Xing; Xiao, Di; Yu, Mingyang (Frontiers in Public Health, 2025)
Spatial epidemiology, as an important branch of epidemiology, has undergone a significant paradigm shift from infectious disease prevention and control to chronic disease management. This paper systematically reviews the application progress of spatial epidemiology in the study of infectious diseases (e.g., malaria, HIV) and chronic diseases (e.g., cancer, cardiovascular diseases), focusing on its role in identifying spatial distribution patterns of diseases, assessing environmental exposures, and supporting health decision-making. The paper compares the differences in data characteristics, analytical methods, and modeling strategies between infectious and chronic diseases, and discusses the impact of multi-scale analysis, data aggregation, and the Modifiable Areal Unit Problem on research results. Furthermore, this paper reviews the innovative value of Geographic Information Systems, remote sensing technology, mobile positioning, and multi-source data fusion in promoting precision public health practices. Finally, the article points out the current challenges faced by spatial epidemiology in privacy ethics, causal inference, and model robustness, and prospects future directions such as AI-enabled multi-omics integration and spatial decision support systems under global health governance.